History of the World Society for Pediatric and Congenital Heart Surgery: The First Decade. Issue 4 (July 2018) - Jacobs, Jeffrey P.; Tchervenkov, Christo I.; Stellin, Giovanni; Kurosawa, Hiromi; Mavroudis, Constantine; Jatene, Marcelo B.; Al-Halees, Zohair; Cicek, Sertac M.; Sandoval, Nestor F.; Backer, Carl L.; Cervantes, Jorge; Dearani, Joseph A.; et al.
The World Society for Pediatric and Congenital Heart Surgery (WSPCHS) is the largest professional organization in the world dedicated to pediatric and congenital heart surgery. The purpose of this article is to document the first decade of the history of WSPCHS from its formation in 2006, to summarize the current status of WSPCHS, and to consider the future of WSPCHS. The WSPCHS was incorporated in Canada on April 7, 2011, with a head office in Montreal, Canada. The vision of the WSPCHS is that every child born anywhere in the world with a congenital heart defect should have access to appropriate medical and surgical care. The mission of the WSPCHS is to promote the highest quality comprehensive cardiac care to all patients with congenital heart disease, from the fetus to the adult, regardless of the patient's economic means, with an emphasis on excellence in teaching, research, and community service.